RABUM TAREE DU YHONG - Wichasawat, Phannaphat; Maicharoen, Prajak (Phranakhon Rajabhat Research Journal : Humanities and Social Sciences, 2024)
The creation of “Taree Du Yhong Dance” performance found that those who watched this performance realized the importance of dugongs and worked together to conserve dugongs for eternity. The performance elements were found as follows; 1) Naming the performance set from the local language of the villagers and giving it the name “Rabum Taree Du Yhong or Taree Du Yhong Dance”. 2) Music creation by studying the melodies of folk songs in the lower south part of Thailand and then, composing a new song called “Rabum Taree Du Yhong or Taree Du Yhong Dance”. 3) Dance postures were created from the behavior of dugongs in 20 different poses. 4) Costume is based on the idea of ​​imitating a dugong in control of the skirt and the color of the dress. The shirt is derived from a Banong shirt with the neckline from a Baba shirt and the sleeves are extended to flare out. 5) Makeup is focused on beautiful styling and hair grabbing in a tight and low bun with face shield and there is a small dugong on top of the head. 6) Performers selection is all women with the same height.